Indolent Angiomatoid Fibrous Histiocytoma Mimicking a Benign Cystic Tumor - Jiro Ichikawa; Tomonori Kawasaki; Kojiro Onohara; Masanori Wako; Satoshi Ochiai; Tetsuo Hagino; Hirotaka Haro (Diagnostics)
Angiomatoid fibrous histiocytoma (AFH) is a rare intermediate tumor that is often difficult to diagnose radiologically and pathologically. Herein, we report a case of AFH in the knee that was initially misdiagnosed as a cystic lesion. The tumor was first identified eight years earlier during the patient’s initial visit, when plain magnetic resonance imaging (MRI) was performed, leading to a diagnosis of a cystic lesion. At the current visit, the tumor had subsequently enlarged, and pain had appeared. Contrast-enhanced MRI was performed at our hospital, revealing enhancement suggestive of a solid tumor. A needle biopsy was performed, raising suspicion of AFH. Wide resection was performed, and AFH was diagnosed using histopathological findings and fluorescence in situ hybridization (FISH). Although there are several characteristic imaging findings of AFH, they are non-specific, and small tumors can be easily overlooked. Furthermore, histopathological findings lack specific immunohistochemical markers, making morphological appearance, combined with FISH findings recently reported as useful, important for preventing misdiagnosis. Since cystic lesions can occur in various locations besides the knee, it is recommended to perform contrast-enhanced MRI for accurate diagnosis when there is an increase in size or the appearance of symptoms, as plain MRI alone may lead to misdiagnosis.